The Convex Relation between Equity Value and Earnings - cynthia utama; roy sembel; siddharta utama (The Indonesian Journal of Accounting Research, 2013)
This paper applies the Burgstahler and Dichev (1997) equity valuation model on stocks listed in the Jakarta Stock Exchange for the period 1993-1996. The prediction of the model is that the value of equity is a convex function of both expected earnings and book value. The piece-wise regression and the quadratic regression are employed to test the prediction. The empirical evidence strongly supports the prediction of convexity: as the ratio of earnings to book value increases, the relation between equity value and earnings becomes stronger while the relation between equity value and book value becomes weaker. In the pooled regression, the quadratic regression provides better explanation on the variation of equity value than the piece-wise regression. Finally, the results are robust with respect to alternative variable/model specifications. The results support Burgstahler and Dichev’s findings in the United States and imply that equity value is a function of both expected earnings and book value.